Organizational Ecology: Past, Present, and Future Directions - Amburgey, Terry L.; Rao, Hayagreeva (Academy of Management Journal, 1996)
We situate the Special Research Forum on Organizational Ecology in the program of ecological research on organizations. We begin with a broad description of organizational ecology's theoretical and empirical development based on the contents of prior collections of work in the field. We then highlight key issues facing ecological research, outline how the articles in this special research forum are linked by common threads, and discuss their contributions. We close with suggested directions for future research.